Introduction to Oil Spinner Machine Tools at SMK Negeri 04 Medan - Roza, Indra; Siregar, Lisa Adriana; Sawitri, Dara; Ananda, Yussa; Nst, Agus Almi; junaidi, J (LPPM STIKOM Tunas Bangsa, 2024)
AbstractThe introduction of oil spinner machines at SMK Negeri 04 Medan is part of a community service program that aims to improve students' knowledge and skills in the field of oil processing technology. An oil spinner machine is a tool used for the process of separating oil from raw materials, which has important applications in the food processing industry and agricultural raw materials. This program is carried out in the form of workshops and direct demonstrations involving students and teachers of SMK Negeri 04 Medan. The main objective of this activity is to provide an in-depth understanding of the function, working principle, and operation of oil spinner machines, as well as the benefits of this technology in industry. In addition, participants are given the opportunity to operate the machine directly and understand its practical application in the oil production process. During the activity, the material presented includes an explanation of the working principle of the oil spinner machine and its role in the oil processing process. Direct practice using an oil spinner machine to process various raw materials and see the results. Information on machine maintenance and safety procedures during operation. The results of this community service show an increase in students' understanding of oil processing technology as well as an increase in practical skills in using oil spinner machines. This activity also provides insight into career opportunities in the oil processing industry and helps prepare students to enter the workforce with relevant technical skills. Overall, this program successfully achieved its objectives and had a positive impact on engineering education at SMK Negeri 04 Medan, as well as strengthening the relationship between educational institutions and industry.